Compliance costs of corporate income taxation in malaysia, 1995 - Loh, A.; Ariff, M.; Ismail, Z.; Shamsher, M.; Ali, M. (Emerald, 1997)
This is the first report on estimates of tax compliance costs of Malaysian companies. Compliance cost is an unavoidable cost of doing business and arises from activities associated with the reporting of income for tax purpose. The average compliance cost per company was estimated to be RM68,836, which is RM0.26 per RM 1,000 sales turnover. Sixty-one percent of compliance cost was incurred in computation-related activities and 39 percent in tax planning activities. Measured relative to revenue, the compliance cost is higher for smaller companies than for larger companies, which suggests that compliance cost is regressive, a finding similar to those reported in other countries.